ASSOCIATION BETWEEN FORMALDEHYDE VAPOR EXPOSURE AND EYE IRRITATION AND UPPER RESPIRATORY TRACT IRRITATION DURING ANATOMY LABORATORY SESSIONS - Silphia Novelyn; Morado Natanael Sidauruk; Reinne Natali Christine (Bajang Institute, 2026)
Formaldehyde is routinely used to preserve cadavers for anatomy practicums; however, volatilization releases airborne formaldehyde that can acutely irritate the eyes and upper respiratory tract. According to the WHO, irritation may be triggered at 0.08–2.52 ppm during 30 minutes of exposure. This comparative cross-sectional study involved 130 medical students (Faculty of Medicine, Universitas Kristen Indonesia/UKI; 2020 cohort) and examined the association between measured formaldehyde concentrations and acute irritative symptoms during anatomy practicum. Air measurements in the practicum room were 0.595 ppm (intact cadaver specimens) and 0.395 ppm (organ specimens), both reported to exceed the WHO limit and Indonesia’s Ministry of Manpower (PERMENAKER) threshold. The most common eye symptoms were eye stinging/pain (n=119; 91.5%), watery eyes (n=102; 78.5%), red eyes (n=42; 32.2%), and itchy eyes (n=37; 28.5%), with additional complaints including a history of eye irritation (n=22; 29.2%), eye discomfort (n=19; 14.6%), and eye swelling (n=11; 8.5%). Upper respiratory symptoms included nasal stinging (n=75; 57.7%), runny nose (n=57; 43.8%), shortness of breath (n=32; 24.6%), sneezing (n=25; 19.2%), cough (n=24; 18.5%), difficulty swallowing (n=17; 13.1%), nausea/vomiting (n=16; 12.3%), hoarseness (n=14; 10.8%), and itchy throat (n=10; 7.7%).